La vulnerabilidad social como un escenario de horror en la obra Sacrificios Humanos de María Fernanda Ampuero - Idrobo Cabrera, Deysi Alexandra (2023)
This research was created with the purpose of analyzing how horror in María Fernanda Ampuero's work "Sacrificios humanos" arises from the situations of social vulnerability experienced by its female characters. To achieve this, we carried out a documentary research and literary analysis in order to interpret the categories of social vulnerability situations and elements of horror. The present literary study examined the characters from a sociological point of view and used poststructuralism as a theoretical basis, specifically Judith Butler's postulates on the body and power relations. Additionally, the approach to vulnerability involves an examination of violence. These concepts derive from horror and cause a mixture of repulsion and fascination resulting from violent storytelling. Therefore, the revision of key concepts on fear were necessary, ranging from Freud, Delumeau, Kristeva, and Carroll to the differences between two genres as closely related as terror and horror. Likewise, two types of horror are distinguished: the real one, a term by Rodas (2016), and horror as a literary genre, as defined by Carroll (1990). The results show that the social vulnerability situations of female characters are determined by the different levels of discrimination and violence based on ethnicity, social class, age, gender, economy, mobility situation, and even non-prototypical bodies. There are many violations based on gender, femicide, rape, infidelity, labor discrimination, psychological, physical, economic, symbolic violence, etc. This representation of vulnerability in Ampuero's work is linked to horror by exposing her characters to atrocious and inhuman experiences in interaction with others. That is, horror arises from the social vulnerability situations experienced by the characters through violence.